DYNAMIC ASSESSMENT OF WORD LEARNING STRATEGIES WITH A CHILD WITH ASD - Reynolds, Abby K. (My University, 2015)
This study compared the use of two different word learning strategies with a child with Autism Spectrum Disorder (ASD): a dynamic assessment approach (i.e., DATMA) and a narrative-based approach. The participant was a child in grade 6 previously diagnosed with ASD and currently receiving speech-language therapy that included addressing vocabulary. The child was taught a set of fourteen words using the two strategies, and then retested on his knowledge of the words a week later. Findings showed that the participant defined words more readily that had been taught using the DATMA approach. He also generalized the strategy to words that had been taught using the narrative-based approach.